2022
DOI: 10.3847/2041-8213/ac7b8a
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the X-Ray Flare from MAXI J0709–159 Using Optical Spectroscopy and Multiepoch Photometry

Abstract: We present a follow-up study on the recent detection of two X-ray flaring events by MAXI/Gas Slit Camera observations in soft and hard X-rays from MAXI J0709–159 in the direction of HD 54786 (LY CMa), on 2022 January 25. The X-ray luminosity during the flare was around 1037 erg s−1 (MAXI), which got reduced to 1032 erg s−1 (NuSTAR) after the flare. We took low-resolution spectra of HD 54786 from the 2.01 m Himalayan Chandra Telescope and the 2.34 m Vainu Bappu Telescope (VBT) facilities in India, on 2022 Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…From the best-fit model, the absorbed and absorption-corrected 2-10 keV fluxes were estimated to be 6 ± 1 × 10 −13 and 6 +3 −1 × 10 −13 erg cm −2 s −1 , respectively. These spectral parameters are consistent with those given by Bhattacharyya et al (2022) which utilized the same NuSTAR data.…”
Section: Time-averaged Spectrumsupporting
confidence: 86%
See 3 more Smart Citations
“…From the best-fit model, the absorbed and absorption-corrected 2-10 keV fluxes were estimated to be 6 ± 1 × 10 −13 and 6 +3 −1 × 10 −13 erg cm −2 s −1 , respectively. These spectral parameters are consistent with those given by Bhattacharyya et al (2022) which utilized the same NuSTAR data.…”
Section: Time-averaged Spectrumsupporting
confidence: 86%
“…The EW of the Hα line was estimated to be −23 Å with an uncertainty of ∼ 15 %. Bhattacharyya et al (2022) also performed optical follow-up observations and reported that the Hα EW was −17.6 Å on February 2 and −16.9 Å on February 3. The results suggest that the EW might change in these 3 days.…”
Section: Summary Of Maxi J0709-159 Activities With Past and Follow-up...mentioning
confidence: 99%
See 2 more Smart Citations
“…In Gaia Early Data Release 3, the distance is estimated to be D = 3.03 +0.31 −0.27 kpc (Bailer-Jones et al 2021). 2 From optical follow-up observations and archival data analysis, Bhattacharyya et al (2022) suggested that LY CMa could be an evolved Be star, rather than a main sequence star or a supergiant. A radio observation was carried out on 2022 January 31 with the MeerKAT radio telescope, but no significant emission was detected at 1.28 GHz and the 3σ upper limit was estimated to be 57 μJy (Rhodes et al 2022) Finally, the Swift ToO observation was carried out on 2022 February 23.…”
Section: Introductionmentioning
confidence: 99%